Absorption-enhanced steam gasification of biomass for hydrogen production: Effects of calcium-based absorbents and NiO-based catalysts on corn stalk pyrolysis-gasification. (2nd March 2017) - Li, Bin; Yang, Haiping; Wei, Liangyuan; Shao, Jingai; Wang, Xianhua; Chen, Hanping
Abstract: Effects of several calcium-based absorbents and NiO-based catalysts on absorption-enhanced pyrolysis-gasification of corn stalk for H2 production were investigated in a two-stage fixed-bed reactor. The results indicated that the addition of calcined CaCO3, calcined limestone, and calcined dolomite significantly improved the concentration and yield of H2 in the product gas because of in situ CO2 absorption and the catalytic effects of the CaO species. The magnesium species in calcined dolomite further catalyzed the gasification process and improved CO2 absorption to increase the concentration and yield of H2 . NiO/CaO bi-functional catalysts/absorbents had a more significant catalytic effect on the gasification process than calcined dolomite: although the H2 concentration in the product gas was lower, the yields of H2, CO, and CO2 were higher. A large amount of CO2 generation which could not be sufficiently absorbed resulted in increased concentration and yield of CO2 in the product gas. The addition of the NiO/γ-Al2 O3 catalyst together with calcined dolomite further increased the concentration and yield of H2 in the product gas. A product gas with a maximum H2 concentration of 85.1 vol.% and negligible amounts of CO2 and C2+ was obtained at a NiO loading of 15 wt.%. Highlights: H2 production was enhanced via CO2 absorption and catalysis of CaO species. Mg in calcined dolomite catalyzed the gasification process and CO2 absorption. NiO/CaO had better enhancing effect on gasification compared to calcined dolomite. 85.1 vol.% H2 was obtained using 15 wt.% NiO/γ-Al2 O3 and calcined dolomite.